Pemanfaatan Biochar Dari Limbah Pertanian Sebagai Pembenah Tanah Untuk Meningkatkan Kapasitas Tukar Kation - * Iwan (Jurnal Ilmu Agroteknologi Indonesia, 2026)
The utilization of biochar derived from agricultural waste as a soil amendment represents an effective and sustainable approach to enhancing soil cation exchange capacity (CEC). This study aims to evaluate the potential of biochar produced from various agricultural residues to improve soil chemical properties, particularly CEC, and to assess the mechanism through which biochar enhances soil fertility. Biochar was produced through closed pyrolysis at temperatures of 350–500°C and subsequently applied to acidic soils commonly found in Indonesian agricultural land. The results show that biochar application significantly increases CEC by enhancing surface negative charges, raising soil pH, and adding stable organic carbon. Additionally, biochar improves soil physical and biological properties, including porosity, water-holding capacity, and microbial activity. Overall, the use of biochar derived from agricultural waste provides substantial agronomic and ecological benefits and serves as an environmentally friendly waste-management strategy. These findings indicate that biochar has strong potential as a sustainable soil amendment technology to increase agricultural land productivity.